ECONOMIC VULNERABILITY AND EARTHQUAKE HAZARD POTENTIAL ANALYSIS AS THE DEVELOPMENT PLANNING RECOMMENDATION DKI JAKARTA PROVINCE - Ahmad Rowatul Irham; Pandu Adi Minarno (Republic of Indonesia Defense University, 2023)
Development planning is essential in reducing damage and losses caused by disasters. Development planning in an area can look at the vulnerabilities in the area, from social vulnerability, physical vulnerability, economic vulnerability, and social vulnerability. Disaster mitigation-based development planning is urgently needed in an area to reduce the impact of disasters. However, many regions still have not paid attention to the importance of disaster mitigation in development planning. One type of disaster mitigation-based development planning that can be applied is to build an area or community that is resilient to disasters by taking into account the frequency and impact of disasters, also economic vulnerability due to these disasters, especially in areas around subduction zones that have a depth of fewer than 40 meters (megathrust zone). DKI Jakarta Province is one of Indonesia's provinces, located around the subduction zone. A hazard analysis using the value of peak ground acceleration in bedrock and economic vulnerability will map the impact of risks that will occur due to an upcoming earthquake so that it can be a recommendation for each municipality in determining development plans.